1996
DOI: 10.1046/j.1365-2362.1996.150293.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of catecholamines in platelet function: pathophysiological and clinical significance

Abstract: Platelets are involved in the pathogenesis of vascular damage in both atherosclerosis and arterial hypertension. Their reactivity in vivo is influenced by different factors, including sympathoadrenal activation, plasma levels of atherogenic lipoproteins and haemorrheological changes. In the present review, we examine the modulation of platelet function by the sympathoadrenal system and concentrate on the role of circulating catecholamines in the control of platelet responses. Human platelets exhibit both adren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
107
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(113 citation statements)
references
References 288 publications
(553 reference statements)
2
107
1
Order By: Relevance
“…27 Although the origin of platelet activation in CHF remains to be established, increased platelet activity might be related to elevation of cytosolic free calcium concentrations 28 and to the fact that platelets may be affected by enhanced sympathoadrenal activation and catecholamine release in CHF. 29 In the present study, the observed beneficial effects of ACE inhibitors on plasma fibrinogen and vWF levels may offer a potential explanation for the reduction in (thrombosis related) ischemic events with the use of these agents in clinical trials. 12 The precise mechanism for a reduction in plasma fibrinogen and vWF levels with ACE inhibitors in CHF remains to be established, although in the present study, the changes in plasma fibrinogen and vWF levels did not appear to be directly related to the reduction in blood pressure.…”
Section: Gibbs Et Al Hemorheological Endothelial and Platelet Functionmentioning
confidence: 57%
“…27 Although the origin of platelet activation in CHF remains to be established, increased platelet activity might be related to elevation of cytosolic free calcium concentrations 28 and to the fact that platelets may be affected by enhanced sympathoadrenal activation and catecholamine release in CHF. 29 In the present study, the observed beneficial effects of ACE inhibitors on plasma fibrinogen and vWF levels may offer a potential explanation for the reduction in (thrombosis related) ischemic events with the use of these agents in clinical trials. 12 The precise mechanism for a reduction in plasma fibrinogen and vWF levels with ACE inhibitors in CHF remains to be established, although in the present study, the changes in plasma fibrinogen and vWF levels did not appear to be directly related to the reduction in blood pressure.…”
Section: Gibbs Et Al Hemorheological Endothelial and Platelet Functionmentioning
confidence: 57%
“…The α2-adrenoceptors in platelets are coupled to Gz/Gi protein and are known to mediate aggregation by reducing the level of cyclic AMP (cAMP) and increasing intracellular Ca +2 release (12), finally leading to exposure of fibrinogen receptors (13). Next to Gi protein-mediated cAMP reduction, activation of the PI3K-mediated Akt pathway is also known to be essential to the signaling of epinephrine-induced platelet aggregation and for the potentiation of other agonists (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…There can be direct injury to the blood vessel walls in response to increased blood pressure and increased flow velocity and in response to an exaggerated discharge of catecholamines (eg, epinephrine and norepinephrine). 21,22 Furthermore, catecholamines can initiate other vascular and prothrombotic events that are associated with atherosclerosis such as increased platelet adhesion and aggregation, 23 vascular lipid uptake, 24 and activation of macrophages. 25 Parenthetically, in this study, the prevalence of hypertension was only slightly higher in persons in the high-anger group compared with that in the low-or moderateanger groups.…”
Section: Discussionmentioning
confidence: 99%